Sustaining Filipino unity harnessing indigenous values for moral recovery - Tapales, Proserpina D.; Alfiler, Ma. Concepcion P. (1991)
The series of revolts dated back to the Spanish era down to the 1986 EDSA Revolution concretizes the sporadic sense of unity of the Filipino people during crisis situations. However, once the crisis is resolved, the spirit of unity withers, leaving the nation at the foothold of recovery. The reason behind this is the faulty perspective toward nationalism. The exposure to a motley of cultures created a gap between the privileged few and the masses. Western values were forced down our throats disregarding the indigenous ones. What is needed for the nation to take off is to reconcile the meaning of the indigenous core values-kapwa and pakikisama between the elite and the masses, incorporate these in projects / programs involving mass participation and translate these into empowerment of the masses through equal sharing and redistribution. Only then will a sense of shared identity and a truer meaning of nationalism be developed which are necessary for Filipinos to sustain unity.
Keywords: Values; Nationalism; Nationalism and socialism